PENGARUH ANALISIS DATA ENVELOPMENT ANALYSIS (DEA), STOCHASTIC FRONTIER APPROACH (SFA), DISTRIBUTION FREE APPROACH (DFA), DERIVASI FUNGSI PROFIT DAN BOPO TERHADAP PERBANDINGAN EFISIENSI KINERJA PERBANKAN SYARIAH DI INDONESIA - Andri Novius; Jasmina Syafe'i; Febri Delmi Yetti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
The purpose of this research to analyze the performance of Islamic Banks in Indonesia as measured by efficiency. Measurement of the efficiency of Sharia/Islamic Banks (BUS) using an alternative method that is the Stochastic Frontier Analysis (SFA) derivation function of profit of efficiency BUS owned by the National Government National Private belongs to test the hypothesis using two sample mean test.The data used in this research is secondary data, obtained through the website of Bank Indonesia from 2011 to 2014. The analysis can describe the condition of Sharia Commercial Bank National Government and the National Private Banks.The results show that the method of calculation of efficiency with Stochastic Frontier Analysis results show that the greater part of Sharia is not efficient in terms of profit earned; the average ratio of BOPO in Sharia Business Unit (UUS) is above 90% which indicates inefficient, so the efficiency is measured by the method of derivation function SFA profit and ROA shows the results are not much different; the average efficiency of Syariah Business Unit of the National Government with the Commercial Bank Syariah Business Unit of the National Private Banks using the method of measuring the efficiency of the SFA derivation function of profit were not significantly different; two sample mean test results using two tailed on the average efficiency of Sharia Commercial Bank National Government and the National Private Banks were calculated from the BOPO ratio. So that the average efficiency hypothesis Sharia Commercial Bank National Government and the National Private Banks are no different or the differences are not significant.